Lingkungan Sekolah sebagai Faktor Penentu Tingkat Motivasi Kerja Guru di Sekolah Dasar - Huriatya, Siti; Ansar; Mattalatta; Kurniawaty (LPPM STIE Tri Dharma Nusantara - Makassar, 2025)
This study aims to examine the influence of the school environment on the motivation of elementary school teachers in Bantaeng District, Bantaeng Regency, South Sulawesi Province. The population elements in this study were all elementary school teachers from Bantaeng District, Bantaeng Regency, South Sulawesi Province, totaling 390 people. Sampling used probability sampling with the stratified random sampling method so that the sample in this study amounted to 150 people. This study consists of school environment variables with indicators of adequate work facilities, a harmonious work climate, fair and supportive leaders and the dependent variable is work motivation. The analysis method used in this study is correlation analysis and t-test. This study found the equation Y = = 0.032 + 0.752X1 + 0.102X2 +0.335X3. The correlation between adequate work facilities and teacher motivation is very strong with a value of 0.831, followed by the correlation between fair and supportive leaders and teacher motivation with a correlation value of 0.742, and finally the correlation between a harmonious work climate and teacher motivation of 0.622.